Sous l’empire de la folie : Moby-Dick, Shakespeare & compagnie - Michel Imbert (Transatlantica)
This article aims at translating Moby-Dick back into Shakespeare’s ornate lingo, and back again into a Swiftian or Sternian brand of “jabberwocky,” in order to expose the sheer nonsense that underlies lame attempts at standing for the Body Politic called Leviathan, understanding it, or making sense of the whale as a whole.